2008
DOI: 10.3174/ajnr.a0966
|View full text |Cite
|
Sign up to set email alerts
|

Substantia Nigra MR Imaging Signal Changes and Cardiomyopathy Following Prenatal Exposure to Cocaine and Heroin: Fig 1.

Abstract: SUMMARY: Exposure to cocaine in utero results in behavioral and neurodevelopmental abnormalities that persist into adulthood. Conventional MR imaging has generally failed to reveal the expected structural lesions to explain these clinical findings. We report a case of focal MR imaging signalintensity changes in the substantia nigra, locus ceruleus, and other selected nerve tracts and nuclei in a child exposed prenatally to cocaine and other drugs. The patient also had dilated cardiomyopathy. Maternal cocaine u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Subsequent reports have been described across Europe [2,3,5,7,9,14,[20][21][22][24][25][26][27][28][29][30], in the USA [6,12,17], Austra- lia [23], Canada [8,11,13,16], as well as a few cases from Taiwan [10,18,19] and Hong Kong [15]. However, reports of heroin-associated leukoencephalopathy remain seldom considering the large number of heroin addicts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent reports have been described across Europe [2,3,5,7,9,14,[20][21][22][24][25][26][27][28][29][30], in the USA [6,12,17], Austra- lia [23], Canada [8,11,13,16], as well as a few cases from Taiwan [10,18,19] and Hong Kong [15]. However, reports of heroin-associated leukoencephalopathy remain seldom considering the large number of heroin addicts.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, as similar leukoencephalopathies have been reported in people using heroin by other means than inhaling heroin vapor [17,19,[22][23][24][25], it is arguable if heroin itself is toxic and/or if the way of heroin application matters.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the volumetric differences, particularly thinner cortex in part of the right lateral OFC, may be moderately involved in cognitive and behavioral difficulties more frequently experienced by opiate and poly-substance-exposed children. Arnold et al (2008) found that exposure to cocaine in utero results in behavioral and neurodevelopmental abnormalities that persist into adulthood. The authors report a case of focal MR imaging signal-intensity changes in the substantia nigra, locus ceruleus, and other selected nerve tracts and nuclei in a child exposed prenatally to cocaine and other drugs.…”
Section: Imaging Cognitive Deficits In Children Exposedmentioning
confidence: 99%
“…Toxic leukoencephalopathies have been more commonly described after heroin smoking, but also after heroin injection [5][6][7], intranasal administration [7], ingestion [8], and intrauterine transmission [9].…”
mentioning
confidence: 99%